The Influence of Investor Sentiment and Market Uncertainty on the Volatility of Gold Sector Stocks on the Indonesia Stock Exchange - Kurnia Permana; Muhammad Haris Saputra; Try Syeftiani (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the influence of investor sentiment and market uncertainty on the volatility of gold sector stocks on the Indonesia Stock Exchange. Although gold stocks are often perceived as a hedging asset, stock price fluctuations in this sector exhibit relatively high volatility, especially during periods of market uncertainty. This study uses a quantitative approach with an explanatory research design and utilizes secondary data in the form of panel data. The research sample consists of gold sector companies listed on the Indonesia Stock Exchange during the 2015–2024 period, selected using a purposive sampling technique. Stock volatility is measured using the standard deviation of stock returns, investor sentiment is proxied by the stock trading activity indicator, and market uncertainty is measured using the market volatility indicator. Data analysis was conducted using panel data regression with a fixed effects approach, accompanied by testing for moderating effects. The results show that investor sentiment has a positive and significant effect on gold sector stock volatility. Furthermore, market uncertainty also has a positive effect on stock volatility and is proven to strengthen the influence of investor sentiment on gold sector stock volatility. These findings support the behavioral finance perspective that emphasizes the role of non-fundamental factors in stock market dynamics. This research provides an empirical contribution in enriching the behavioral finance literature in the context of emerging markets and provides practical implications for investors, issuers, and regulators in managing capital market risk and stability.